1988
DOI: 10.1111/j.1476-5381.1988.tb11466.x
|View full text |Cite
|
Sign up to set email alerts
|

Single ionic channels induced by palytoxin in guinea‐pig ventricular myocytes

Abstract: 1Mechanisms of palytoxin-induced ion permeability were examined in isolated single ventricular cells of guinea-pig under whole-cell-attached patch clamp conditions. 2 Palytoxin (1-2 x 10-1 M, dissolved in Tyrode solution and put in the patch electrode) induced an elementary current flowing through single channels. Direction of the current was inward and the amplitude was 0.65 + 0.03 pA (mean + s.e. mean) at the resting membrane potential. The amplitude increased linearly with membrane hyperpolarization and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 31 publications
(25 reference statements)
7
39
0
Order By: Relevance
“…In line with the observations in ventricular myocytes (2,20,27,35), we found that palytoxin generated a very similar current in atrial myocytes. In particular, the palytoxin-induced current displayed a linear I-V relationship that was reversed at ϳ5 mV, was comparable in magnitude, and could be antagonized by cardiac glycosides.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In line with the observations in ventricular myocytes (2,20,27,35), we found that palytoxin generated a very similar current in atrial myocytes. In particular, the palytoxin-induced current displayed a linear I-V relationship that was reversed at ϳ5 mV, was comparable in magnitude, and could be antagonized by cardiac glycosides.…”
Section: Discussionsupporting
confidence: 78%
“…In mammalian ventricular myocytes, palytoxin induces opening of nonselective cation channels permeable to Na ϩ and K ϩ by converting the Na ϩ -K ϩ pump into a channel (2,20,27,35). At negative holding potentials, the palytoxininduced inward current is carried mainly by Na ϩ and can be inhibited by cardiac glycosides (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, left panel). This pathway could be the non-selective cationic channel that has recently been shown to be activated by PTX in rat cardiomyocytes [29,30] and for which no inhibitor is yet available. The question whether the same channel is responsible for the increased H+ and ethylisopropylamilorideinsensitive Na+ transports cannot be answered easily for unitary H+ currents are too small to be detected in patch clamp recordings.…”
Section: Resultsmentioning
confidence: 99%
“…The following lines of evidence established that PTX interacts with the Na + / K + pump itself: (1) PTX induced ouabain-sensitive cation flux in yeast cells (which lack endogenous Na + /K + pumps) just after the expression of both Na + /K + -ATPase α-and β-subunits, and not of either subunit alone (Scheiner-Bobis et al 1994) (2) incorporation of in vitro-translated Na + /K + -ATPase α-and β-subunits into lipid bilayers allowed PTX to open cation channels with a unitary conductance of about 7 pS (Hirsh and Wu 1997) similar to that of the relatively nonselective channels opened by PTX in various excitable tissues Ikeda et al 1988;Muramatsu et al 1988;Rakowski et al 2007). …”
Section: Palytoxinsmentioning
confidence: 99%